Comprehensive Annotation of Complete ABO Alleles and Resolution of ABO Variants by an Improved Full-Length ABO Haplotype Sequencing. - Ying, Yanling; Zhang, Jingjing; Hong, Xiaozhen; Yuan, Wenjing; Ma, Kairong; Huang, Xinyu; Xu, Xianguo; Zhu, Faming (Clinical Chemistry, 2025)
Background Full-length ABO haplotype sequencing is crucial for accurate genotyping, reference gene annotation, and molecular mechanism analysis of its variants. However, there is currently a deficiency of comprehensive annotation for full-length ABO haplotypes, spanning from the 5′ untranslated region (UTR) to the 3′ UTR. Methods Two sets of specimens (79 random blood donors and 47 ABO variants) were tested. The full-length ABO gene spanning the 5′ UTR to the 3′ UTR was amplified using an improved one-step ultra-long-range PCR with a pair of PCR suppression primers. A single-molecule real-time library was constructed, and ABO haplotype sequencing was performed. Data analysis including basecalling, aligning, variant calling, clustering, and variant annotation were performed. Results The amplicon measured 26.1 kb without splicing, representing the most complete ABO gene reported to date. The complete ABO haplotype sequence was obtained via long-read sequencing. The comprehensive ABO reference alleles were obtained and the ABO sequence patterns within each allele in a Chinese population were further classified. The full-length ABO gene haplotype analysis technique effectively resolved ABO variants with structural variations (SVs), including large fragment deletions, inversions, recombination, and chimeras. Conclusions Full-length ABO haplotype sequencing filled a gap that was missing with respect to the 3′ UTR sequences of ABO alleles and can advance blood group genomic analysis, aiding in ABO gene function analysis, evolutionary studies, and the resolution of ABO variants.